European Sovereignty and Sustainable Development: Disenchanted Analysis of a Clear-Obscure Political Speech - Nathalie Hervé-Fournereau (Vasyl Stefanyk Precarpathian National University, 2018)
This article demonstrates the new innovative approach to the significant legal and political correlations and is been written in the form of Presidential political speech analysis, which foresees the deep synthesis and knowledge of legislative provisions, reflections on national sovereignty, ecological transition, climate change and European Union legislation.